2010
DOI: 10.4323/rjlm.2010.239
|View full text |Cite
|
Sign up to set email alerts
|

Morphological diagnosis of hyperthermia-related deaths

Abstract: Hyperthermia, characterized by a core temperature of over 40 o C, occurs when the body's thermoregulatory mechanisms are no longer able to dissipate heat. From a clinical point of view hyperthermia can be of three main types: (1) a consequence of an imbalance between anti and pro-inflammatory agents (usually in septic conditions), (2) heatstroke and (3) malignant hyperthermia. Death caused by hyperthermia, either heatstroke or malignant hyperthermia, is diagnosed at the autopsy mainly using seric, histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We observed that the fatal hyperthermia group contained a lower content in both glycogen and lactate in comparison with the normothermia group. This is understandable as the raised body temperature during the early pathological process of hyperthermia increases the metabolic rate and oxygen consumption, resulting in the consumption of carbohydrates [ 88 ]. Additionally, Figure 7 D shows that the fatal hypothermia group has a more active glycolysis process than the hyperthermia group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the fatal hyperthermia group contained a lower content in both glycogen and lactate in comparison with the normothermia group. This is understandable as the raised body temperature during the early pathological process of hyperthermia increases the metabolic rate and oxygen consumption, resulting in the consumption of carbohydrates [ 88 ]. Additionally, Figure 7 D shows that the fatal hypothermia group has a more active glycolysis process than the hyperthermia group.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, our experimental results reveal a longer average death time for rats in the fatal hypothermic tissue group than those of the fatal hyperthermic group. Previous literature has reported that heat stress not only directly affects the central nervous system and induces cytotoxicity, which kills cells, but also indirectly induces blood redistribution toward skin and muscles, resulting in neuronal necrosis [ 81 , 88 ]. We speculate that the fatal hypothermia group underwent a longer period of ischemia than the fatal hyperthermia group, which led to the more active glycolysis seen in the fatal hypothermia group.…”
Section: Resultsmentioning
confidence: 99%
“…Paradoxically, it is generally accepted that there are no specific autopsy findings for hyperthermia (12, 13). The reason that academia accepts this in hyperthermia and not hypothermia are not known; perhaps it is a quirk of human nature.…”
Section: Discussionmentioning
confidence: 99%
“…The average body core temperature is near 37 • C in humans [94], while hypothermia is defined as a body core temperature below 35 • C. Hypothermia can be considered a medical emergency if the body temperature falls below 32 • C, which results in multiple organ failure and even death (at hypothermia levels between 35 • C and the critical value of 32 • C, there are potentially severe consequent conditions such as blood hypercoagulability, with thrombogenic risk and immune suppression, which is prone to infection) [95]. The concept of cooling therapy comes from hibernation in some mammalian species, which results in a lowered body temperature and slowed metabolism.…”
Section: Systemic Hypothermia (Selective Local Brain) Coolingmentioning
confidence: 99%